Synopsis of My Contribution to Plant and Crop Science - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2015)
I publishedabout 500 papers on various disciplines of botany related to the development of low cost technology and its utilization in mass scale screening of pipe line crop cultivars and varieties for resistance to abiotic stresses such as salinity, drought, heat stress, flooding of various field and vegetable crops. We identified 63 species belonging to different families showing great biodiversity and biology. Though few studies were undertaken on the growth and development of fibre cells in jute, but insignificant studies were undertaken on the growth and anatomy of other baste fibre crops.Few research inputs have been undertaken on pearl millet genotypes introduced in Mexico in Nuevo Leon and highlands of Puebla through bachelor and doctorate thesis of students.Using simple low cost technology I evaluated and selected crop cultivars of cotton, sunflower and castor for tolerance to drought, salinity and heat stress.Though significant progress has been obtained in breeding crop cultivars, under high input situations, but insignificant progress has been directed in increasing productivity under sustainable agriculture in the farmers’ fields. We selected few species with high carbon fixation such as Eugenia caryophyllata 51.66%, Litsea glauscensens 51.34 % etc.